Nonspecific DNA Binding and Bending by HU(αβ): Interfaces of the Three Binding Modes Characterized by Salt Dependent Thermodynamics - Koh, Junseock (2011)
Previous ITC and FRET studies demonstrated that Escherichia coli HU(αβ) binds nonspecifically to duplex DNA in three different binding modes: a tighter-binding 34 bp mode which interacts with DNA in large (>34 bp) gaps between bound proteins, reversibly bending it 140° and thereby increasing its flexibility, and two weaker, modestly cooperative small-site-size modes (10 bp, 6 bp) useful for filling gaps between bound proteins shorter than 34 bp. Here we use ITC to determine the thermodynamics of these binding modes as a function of salt concentration, and deduce that DNA in the 34 bp mode is bent around but not wrapped on the body of HU, in contrast to specific binding of IHF. Analyses of binding isotherms (8, 15, 34 bp DNA) and initial binding heats (34, 38, 160 bp DNA) reveal that all three modes have similar log-log salt concentration derivatives of the binding constants (Sk(i)) even though their binding site sizes differ greatly; most probable values of Sk(i) on 34 bp or larger DNA are − 7.5 ± 0.5. From the similarity of Sk(i) values, we conclude that binding interfaces of all three modes involve the same region of the arms and saddle of HU. All modes are entropy-driven, as expected for nonspecific binding driven by the polyelectrolyte effect. The bent-DNA 34 bp mode is most endothermic, presumably because of the cost of HU-induced DNA bending, while the 6 bp mode is modestly exothermic at all salt concentrations examined. Structural models consistent with the observed Sk(i) values are proposed.